Introducing critical elements of cross-cultural scholarship development: A discussion towards a model - Qi Sun; Haijun Kang (Adult Education Research Conference, 2023)
Theorizing existing literature, we present a model outlining five essential elements to guide cross-cultural scholarship practices. A scenario showcases how to apply these elements to practical situations.
Keywords: cross-cultural scholarship; adult education theories; adult educator